PENYUSUNAN BAHAN AJAR BAGI GURU MTS SATU ATAP OKU (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2020)
This Community Service Activity is located at MTS One Roof Talang Jawa, OKU Regency. The title of the material presented was the Compilation of Teaching Materials for MTS One Roof Talang Jawa Teachers in OKU Regency. The problems with partners in this counseling are as follows: the difficulty of finding appropriate and contextual teaching materials to use in learning activities, the interest of teachers in compiling and developing teaching materials at One Roof MTs is very high. The objectives to be achieved in this community service activity are to provide knowledge to teachers about the process of preparing teaching materials, provide understanding, appeal and socialization about the preparation of teaching materials. On the other hand, the solutions offered to solve the problems faced by partners systematically in accordance with the priority problems that exist in MTS One Roof Talang Jawa, OKU Regency are providing counseling and training regarding the preparation of teaching materials properly and correctly, providing implementation of the preparation of teaching materials properly and true, changing the teacher's mindset and improving the quality, understanding, and skills of teachers in the preparation of teaching materials at MTS Satu Atap Talang Jawa, OKU Regency.